Bokmål og nynorsk som kjelde- og målspråk i internordiske ordbøker - Hovdenak, Marit (LexicoNordica, 2001)
There are many bilingual dictionaries between Norwegian and the other Nordic languages, differing a lot in size, age etc. The paper deals with the use of either of the written standards Nynorsk and Bokmål – or both – as source languages and target languages in these dictionaries. Bokmål developed from Danish, which was the only written language in Norway for centuries. Nynorsk is based on the dialects of Norway and was launched as a written norm for a new Norwegian language about 1850. The linguistic difference between the two standards is relatively small, partly because of spelling reforms. More than half the vocabulary is common to the two standards. The standards are by law given equal official standing, but Bokmål has remained the majority written language. Most bilingual dictionaries from or to Norwegian are in Bokmål, mostly in a more traditional subvariety than the official Bokmål standard. In several of the newer bilingual dictionaries from Norwegian to a Nordic language Bokmål and Nynorsk are united in one list, with common words and forms unmarked, whereas specific words and forms have different markers. In some of the dictionaries the source language is mainly Bokmål, supplemented with the most frequent Nynorsk words. – This way of dealing with the bilingual situation in Norway seems at last partly successful, although it does have its problems. There are also bilingual Nordic dictionaries where the source language is monolingual Nynorsk or Bokmål. As a target language Bokmål is the dominant language. There are a couple of dictionaries with Nynorsk as target language, and one dictionary which combines the two in a somewhat complicated and space-demanding system. It is desirable to have bilingual dictionaries to and from both written standards of Norwegian. It is possible to combine them as source language, but hardly as target language.